Band gap effects of hexagonal boron nitride using oxygen plasma - Singh, Ram Sevak (2014)
Tuning of band gap of hexagonal boron nitride (h-BN) has been a challenging problem due to its inherent chemical stability and inertness. In this work, we report the changes in band gaps in a few layers of chemical vapor deposition processed as-grown h-BN using a simple oxygen plasma treatment. Optical absorption spectra show a trend of band gap narrowing monotonically from 6 eV of pristine h-BN to 4.31 eV when exposed to oxygen plasma for 12 s. The narrowing of band gap causes the reduction in electrical resistance by ∼100 fold. The x-ray photoelectron spectroscopy results of plasma treated hexagonal boron nitride surface show the predominant doping of oxygen for the nitrogen vacancy. Energy sub-band formations inside the band gap of h-BN, due to the incorporation of oxygen dopants, cause a red shift in absorption edge corresponding to the band gap narrowing.